The tapering practices of competitive weightlifters - Winwood, P. W.; Keogh, J. W.; Travis, S. K.; Pritchard, H. J. (The Journal of Strength and Conditioning Research, 2023)
This study explored the tapering strategies of weightlifting athletes. Weightlifting athletes (n = 146) (mean ± SD; age: 29.2 ± 8.7 years, height: 172.5 ± 10.1 cm, body mass: 84.0 ± 17.2 kg, 4.7 ± 3.4 years of weightlifting training experience, and 3.9 ± 3.3 years of competitive weightlifting experience) completed a self-reported 4-page, 39-item internet survey on tapering practices. Subgroup analysis by sex (male and female) and competitive standard (local or regional, national and international level) was conducted. Ninety-nine percent (n = 144) of weightlifting athletes reported they used a taper. Athletes stated that their typical taper length was 8.0 ± 4.4 days, with the linear (36%) and step tapers (33%) being the most performed. Training volume decreased during the taper by 43.1 ± 14.6%, and athletes ceased all training 1.5 ± 0.6 days out from competition. Muscular strength, light technique work, and aerobic conditioning were the most common types of training performed in the taper. Athletes typically stated that tapering was performed to achieve rest and recovery, physical preparation for peak performance and mental preparation; training intensity and training duration decreased whereas training frequency remained the same or decreased; traditional exercises were performed further out from competition than weightlifting exercises; assistance exercises and some strength work were reduced; nutritional changes, foam rolling, static stretching, and massage were strategies used in the taper; and poor tapering occurred because of training too heavy, too hard, or too light and life-work circumstances. These results may aid athletes and coaches in strength sports to optimize tapering variables leading to improved performances.